ISSUES OF IMPROVING THE ACTIVITY OF COMMERCIAL BANKS IN THE FINANCIAL MARKET (Intent Research Scientific Journal, 2023)
The article shows the growing competition between banks and non-bank investment institutions that carry out transactions with securities. In this, banks have great advantages over non-bank investment institutions in terms of their rights, financial base, diversification of assets, personnel composition and material support, and recommendations aimed at further improvement of the activity are given.